Effectiveness of Exhaust Gas Recirculation (EGR) system on reducing NOx pollutants on turbocharged Hydrogen engines - Nguyen, Huu Phuoc; Ngo, Duy Nam; Ngo, Minh Hien; Pham, Van Chien (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2025)
This paper presents a detailed analysis of a six-cylinder, 13.5 L turbocharged hydrogen (H2) fueled spark ignition engine. The engine features direct injection and a low-pressure exhaust gas recirculation (LP EGR) loop. The objective is to demonstrate the engine's performance under various operating conditions using a basic engine control system integrated within the IFP-Engine library of Amesim software. The study successfully highlights the impact of different operating parameters on combustion efficiency and NOx emissions.